MODAL SOSIAL MASYARAKAT PEDULI BENCANA (MPB) DESA TANJUNG LEBAN DALAM PENCEGAHAN KEBAKARAN LAHAN GAMBUT - Erlangga Noor; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study aims to identify and analyze the activities, challenges, social capital and social cohesion of the Community Concerned about Disasters in the village of Tanjung Leban Bengkalis with a qualitative approach. The results of the study show that bonding social capital in MPB activities is in the form of mutual cooperation traditions, activities for making water canals and canal blockings around the residents' gardens. Bridging social capital can be seen from joint activities to revegetate burnt forests with timber plants and plants with economic value such as areca nut and fruits. Linking social capital can be seen from the good relations with institutions inside and outside the village such as the village government. PT. BBHA, Manggala Agni, NGOs, universities, and other institutions that have one goal. Elements of internal and external trust in the group's duties and functions are going well. Likewise with social networks, it can be seen that MPB participates in building networks well, especially at the external level in their work area. The internal norms of the MPB group are strongly intertwined on the basis of personal awareness. A set of rules is established by the MPB for its members, these rules are adhered to even if they are sometimes only verbal. Meanwhile, if there are members who violate the sanctions given are based on deliberative considerations between MPB group members. Social cohesion is created on the basis of a sense of mutual ownership and a common goal of concern in protecting forests and peatlands. Strong social cohesion had a positive impact on MPB institutional performance in reducing the number of forest and peatland fires in Tanjung Leban Village. Keywords: Peatland, Social Capital, Tanjung Leban